THE GEOGRAPHY OF LOGISTIC ACTIVITIES IN WESTERN REGION OF UKRAINE - Грицевич, Володимир; СеньківМар`яна (Human Geography Journal, 2016)
The meaning of “logistic activities” on the base of activityapproach is defined in paper. The geologistics services structure in the Western region of Ukraine is researched. A map diagram showing the territorial distribution of logistics services in the region is created. The spatial location of logistics companies in Western region of Ukraine is analyzed, in particular by calculating the entropy. The list of main logistics operators in region is created and their typology by logistic level is carried out .